Pro-Inflammatory Implications of 2-Hydroxypropyl-β-cyclodextrin Treatment - Houben, Tom; Yadati, Tulasi; de Kruijf, Robbin; Gijbels, Marion J. J.; Luiken, Joost J. F. P.; van Zandvoort, Marc; Kapsokalyvas, Dimitris; Lütjohann, Dieter; Westerterp, Marit; Plat, Jogchum; Leake, David; Shiri-Sverdlov, Ronit (Frontiers in Immunology, 2021)
Lifestyle- and genetically-induced disorders related to disturbances in cholesterol metabolism have shown the detrimental impact of excessive cholesterol levels on a plethora of pathological processes such as inflammation. In this context, two-hydroxypropyl-β-cyclodextrin (CD) is increasingly considered as a novel pharmacological compound to decrease cellular cholesterol levels due to its ability to increase cholesterol solubility. However, recent findings have reported contra-indicating events after the use of CD questioning the clinical applicability of this compound. Given its potential as a therapeutic compound in metabolic inflammatory diseases, in this study, we evaluated the inflammatory effects of CD administration in the context of cholesterol-induced metabolic inflammation in vivo and in vitro. The inflammatory and cholesterol-depleting effects of CD were first investigated in low-density lipoprotein receptor knockout (Ldlr-/) mice that were transplanted with Npc1nih or Npc1wt bone marrow and were fed either regular chow or a high-fat, high-cholesterol (HFC) diet for 12 weeks, thereby creating an extreme model of lysosomal cholesterol-induced metabolic inflammation. In the final three weeks, these mice received daily injections of either control (saline) or CD subcutaneously. Subsequently, the inflammatory properties of CD were investigated in vitro in two macrophage cell lines and in murine bone marrow-derived macrophages (BMDMs). While CD administration improved cholesterol mobilization outside lysosomes in BMDMs, an overall pro-inflammatory profile was observed after CD treatment, evidenced by increased hepatic inflammation in vivo and a strong increase in cytokine release and inflammatory gene expression in vitro in murine BMDMs and macrophages cell lines. Nevertheless, this CD-induced pro-inflammatory profile was time-dependent, as short term exposure to CD did not result in a pro-inflammatory response in BMDM. While CD exerts desired cholesterol-depleting effects, its inflammatory effect is dependent on the exposure time. As such, using CD in the clinic, especially in a metabolic inflammatory context, should be closely monitored as it may lead to undesired, pro-inflammatory side effects.